Draft Annual Plan 1976-77 Himachal Pradesh - Planning Commission (Planning Commission, 1976)
Growth with social justice is the central theme of Planning in the Pradesh, the force of which has “been further strengthened with the introduction of the Point Economic Programme recently announced by the Prime Minister of India Accordingly, in the formulation of this Draft Annual Plan for 1976-77 of this Pradesh, the conscious efforts have been made to realize the objectives of the Economic Programme.
Planning Commission
Planning Commission